Toward Fluorinated Aminoglycosides: Structural Studies of Phenylhydrazine Condensation with Carbohydrate Derivatives - Franconetti, Antonio; Borrachero, Pastora; Gómez-Guillén, Manuel; Cabrera-Escribano, Francisca (Synlett, 2013)
The reaction of phenylhydrazine with a sugar dialdehyde in water, as a key step for the synthesis of the 3-amino-3-deoxy-d-glucose moiety contained in kanamycin, has been revisited. Structural studies (IR and NMR as well as a simple theoretical model based on energy-minimization calculations and MD calculations) reported herein support the observed stereo- and regioselectivity. Efforts to improve the reproducibility and viability of the process as part of a convenient approach towards fluorinated kanamycin are also now presented.
Keywords: carbohydrates; condensation; phenylhydrazine; stereo- and regioselectivity; green chemistry